Cryptographic security solutions for the Internet of Things - Banday, Mohammad Tariq 1969 (Advances in information security, privacy, and ethics (AISPE) book series, 2019)
"This book discusses novel designs and recent developments in the field of low power, low resource cryptographic security control procedures to improve the efficiency of existing security mechanisms that can help in securing sensors, devices, networks, communication and data in the internet of things"--